Performance of local variety mango graft unions under nursery conditions - Ajal, J.; Kizito, Elizabeth. B. (Agricultural Science and Entrepreneurship, 2012)
The performance and graft wound healing in Mangifera indica (local varieties) under nursery conditions has not been taken with great keen despite its role in raising a viable orchard. The objective of this study was to assess graft establishment and success of different local variety mango scions on local rootstocks using splice grafting as a method of propagation. Scion lengths were measured and data on number of leaves, time of bud sprouting and leaf size were subjected to analysis. The analysis revealed that graft union healing and establishment of the local mangoes vary according to the cultivar used. Kate variety registered the highest level of survival of 70 %. There were also differences in the time of bud sprouting of the three varieties. The difference in bud sprouting and graft survival was due to different levels of rootstock-scion compatibility which have implications in wound healing. Studies on improving compatibility levels is needed to increase graft success at nursery level.
Keywords: Mango; Graft wound healing; Local varieties; Nursery